Circulating matrix metalloproteinases are associated with arterial stiffness in patients with type 1 diabetes: pooled analysis of three cohort studies - Peeters, Stijn A. (Cardiovasc Diabetol, 2017)
BACKGROUND: Altered regulation of extracellular matrix (ECM) composition by matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinase (TIMPs) may contribute to arterial stiffening. We investigated associations between circulating MMP-1, -2, -3, -9, -10 and TIMP-1, and carotid-femoral pulse wave velocity (cfPWV) and pulse pressure (PP), as markers of arterial stiffness in type 1 diabetic patients. METHODS: Individuals with type 1 diabetes from three different cohorts were included in this study: EURODIAB Prospective Complications study (n = 509), LEACE (n = 370) and PROFIL (n = 638). Linear regression analyses were used to investigate cross-sectional associations between circulating levels of MMP-1, -2, -3, -9, -10, and TIMP-1 and cfPWV (n = 614) as well as office PP (n = 1517). Data on 24-h brachial and 24-h central PP were available in 638 individuals from PROFIL. Analyses were adjusted for age, sex, duration of diabetes, HbA1c, mean arterial pressure (MAP), and eGFR, and additionally for other cardiovascular risk factors and presence of vascular complications. RESULTS: After adjustment for potential confounders and presence of vascular complications, circulating MMP-3 was associated with cfPWV [β per 1 SD higher lnMMP3 0.29 m/s (0.02; 0.55)]. In addition, brachial and central 24-h PP measurements in PROFIL were significantly associated with MMP-2 [(1.40 (0.47:2.33) and 1.43 (0.63:2.23)]. Pooled data analysis showed significant associations of circulating levels of MMP-1 and MMP-2 with office PP [β per 1 SD higher lnMMP-1 and lnMMP-2 = − 0.83 mmHg (95% CI − 1.50; − 0.16) and = 1.33 mmHg (0.55; 2.10), respectively]. CONCLUSIONS: MMPs-1, -2, and -3 are independently associated with markers of arterial stiffening in patients with type 1 diabetes and may become therapeutic targets. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12933-017-0620-9) contains supplementary material, which is available to authorized users.